SARS-CoV-2 leads to a small vessel endotheliitis in the heart - Maccio, Umberto (EBioMedicine, 2021)
BACKGROUND: SARS-CoV-2 infection (COVID-19 disease) can induce systemic vascular involvement contributing to morbidity and mortality. SARS-CoV-2 targets epithelial and endothelial cells through the ACE2 receptor. The anatomical involvement of the coronary tree is not explored yet. METHODS: Cardiac autopsy tissue of the entire coronary tree (main coronary arteries, epicardial arterioles/venules, epicardial capillaries) and epicardial nerves were analyzed in COVID-19 patients (n = 6). All anatomical regions were immunohistochemically tested for ACE2, TMPRSS2, CD147, CD45, CD3, CD4, CD8, CD68 and IL-6. COVID-19 negative patients with cardiovascular disease (n = 3) and influenza A (n = 6) served as controls. FINDINGS: COVID-19 positive patients showed strong ACE2 / TMPRSS2 expression in capillaries and less in arterioles/venules. The main coronary arteries were virtually devoid of ACE2 receptor and had only mild intimal inflammation. Epicardial capillaries had a prominent lympho-monocytic endotheliitis, which was less pronounced in arterioles/venules. The lymphocytic-monocytic infiltrate strongly expressed CD4, CD45, CD68. Peri/epicardial nerves had strong ACE2 expression and lympho-monocytic inflammation. COVID-19 negative patients showed minimal vascular ACE2 expression and lacked endotheliitis or inflammatory reaction. INTERPRETATION: ACE2 / TMPRSS2 expression and lymphomonocytic inflammation in COVID-19 disease increases crescentically towards the small vessels suggesting that COVID-19-induced endotheliitis is a small vessel vasculitis not involving the main coronaries. The inflammatory neuropathy of epicardial nerves in COVID-19 disease provides further evidence of an angio- and neurotrophic affinity of SARS-COV2 and might potentially contribute to the understanding of the high prevalence of cardiac complications such as myocardial injury and arrhythmias in COVID-19. FUNDING: No external funding was necessary for this study.